Effects of the Ecdysone Receptor on the Regulation of Reproduction in Coccinella septempunctata - Ying Cheng; Yuhang Zhou; Cao Li (Insects)
The effects of the gene encoding the ecdysone receptor (EcR) on the reproduction of the ladybug Coccinella septempunctata was evaluated. EcR transcription was measured by quantitative real-time PCR in ladybug adults reared on artificial diets with and without 20-hydroxyecdysone (20E). EcR expression levels in 5 d old male and female ladybugs supplied with the 20E-amended artificial diet were lower than expression levels in ladybugs reared on an artificial diet lacking 20E. However, EcR expression levels in 10 d old ladybugs supplied with the 20E artificial diet were higher than those lacking 20E supplementation. The regulatory effects of EcR were studied in female and male ladybugs by RNA interference. EcR expression in female ladybugs injected with EcR-dsRNA was significantly downregulated after 5 d but remained unaffected in 10 d old females. EcR expression levels in males microinjected with EcR-dsRNA were significantly lower at 5 and 10 d after microinjection than GFP-dsRNA-treated males. The ovary volume in females injected with EcR-dsRNA at 5 d was smaller than females microinjected with GFP-dsRNA, but volumes at 10 d were larger than in GFP-dsRNA-treated females. The testes of males injected with EcR-dsRNA were larger than those injected with GFP-dsRNA at 5 d but the testes at 10 d after injection with EcR-dsRNA were smaller than those injected with GFP-dsRNA. When females were microinjected with EcR-dsRNA and mated with noninjected males, egg production decreased by 34.80% for 20 days. When males were microinjected with EcR-dsRNA and mated with noninjected females, egg production decreased by 30.38% for 20 days. Injection of female and male ladybugs with EcR-dsRNA had no significant effect on egg hatching rates. Our results show that EcR plays an important role in the development of reproductive organs and egg development in C. septempunctata.